2020
DOI: 10.1007/s00595-020-02133-0
|View full text |Cite
|
Sign up to set email alerts
|

Determining the protective characteristics and risk factors for the development of anastomotic leakage after low anterior resection for rectal cancer

Abstract: Purpose Anastomotic leakage is one of the most serious postoperative complications associated with surgery for rectal cancer. The present study aimed to identify the protective characteristics and risk factors associated with anastomotic leakage after low anterior resection for rectal cancer. Methods This was a retrospective, single-center study conducted between January 2009 and December 2017 at our institution. In total, 136 rectal cancer patients who underwent low anterior resection were included in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In 2021, Suzuki, N et al, ( 48 ) also reported anastomotic complications, such as leakage, which was confirmed to be associated with a 3.5-fold increase in the incidences of major LARS. However, we could not find anastomotic complications increasing the incidences of major LARS in our study, and we thought this was due to the development of operation skills and reliable management of patients after operation in recent years.…”
Section: Discussionmentioning
confidence: 93%
“…In 2021, Suzuki, N et al, ( 48 ) also reported anastomotic complications, such as leakage, which was confirmed to be associated with a 3.5-fold increase in the incidences of major LARS. However, we could not find anastomotic complications increasing the incidences of major LARS in our study, and we thought this was due to the development of operation skills and reliable management of patients after operation in recent years.…”
Section: Discussionmentioning
confidence: 93%
“…In 2021, Suzuki, N et al, [49] also reported anastomotic complications, such as leakage, which was con rmed to be associated with a 3.5-fold increase in the incidences of major LARS. However, we could not nd anastomotic complications increasing the incidences of major LARS in our study, and we thought this was due to the development of operation skills and reliable management of patients after operation in recent years.…”
Section: Discussionmentioning
confidence: 97%
“…We found no further relevant studies in grey literature and handsearching. After excluding irrelevant studies and duplicates, we included 12 studies in the present systematic review and meta-analysis for a total of 2940 patients undergoing GI surgeries, of whom 353 developed AL [4,[15][16][17][18][19][20][21][22][23][24][25]. The PRISMA flow diagram in Fig.…”
Section: Identification Of Relevant Studiesmentioning
confidence: 99%
“…In terms of study design, there were two prospective and 10 retrospective studies. Studies were conducted in China(n = 3) [17,18,25], Italy (n = 2) [19,22], Romania(n = 2) [4,20], Japan(n = 2) [23,24], Indonesia(n = 1) [15], Turkey(n = 1) [16], and Mexico(n = 1) [21]. So, there were six studies on white people, with 2106 patients, of whom 200 developed AL [4,16,[19][20][21][22], and six studies on East Asian people, with 834 patients, of whom 153 developed AL [15,17,18,[23][24][25].…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation